A Ratiometric Calcium Reporter CGf Reveals Calcium Dynamics Both in the Single Cell and Whole Plant Levels Under Heat Stress - Weigand, Chrystle; Kim, Su-Hwa; Brown, Elizabeth; Medina, Emily; Mares, Moises; Miller, Gad; Harper, Jeffrey F.; Choi, Won-Gyu (Frontiers in Plant Science, 2021)
Land plants evolved to quickly sense and adapt to temperature changes, such as hot days and cold nights. Given that calcium (Ca2+) signaling networks are implicated in most abiotic stress responses, heat-triggered changes in cytosolic Ca2+ were investigated in Arabidopsis leaves and pollen. Plants were engineered with a reporter called CGf, an intensio-ratiometric, genetically encoded Ca2+ reporter with an mCherry reference domain fused to Ca2+ reporter GCaMP6f). Changes in [Ca2+]cyt were estimated based on CGf’s apparent KD around 220nM. The ratiometric output provided an opportunity to compare Ca2+ dynamics between different tissues, cell types, or subcellular locations. In leaves, CGf detected heat-triggered cytosolic Ca2+ signals, comprised of three different signatures showing similarly rapid rates of Ca2+ influx followed by differing rates of efflux (50% durations ranging from 5 to 19 minutes). These heat-triggered Ca2+ signals were approximately 1.6-fold greater in magnitude than blue light-triggered signals in the same leaves. In contrast, growing pollen tubes showed two different heat-triggered responses. Heat caused tip-focused steady-growth [Ca2+]cyt oscillations to shift to a pattern characteristic of a growth arrest (22%), or an almost undetectable [Ca2+]cyt (78%). Together, these contrasting examples of heat-triggered Ca2+ responses in leaves and pollen highlight the diversity of Ca2+ signals in plants, inviting speculations about their differing kinetic features and biological functions.